Investigating the impact of the Russian-Ukrainian conflict on the Egyptian market: insights from multiple sectors - Tarek Fatouh; Engy Bayoumi; Micheal Orloff (International Business Logistics Journal, 2022)
Purpose: This research aims at investigating the impact of the Russian-Ukrainian war on the supply chain processes in the Egyptian market. In addition to developing contingency plans that could guide the Egyptian stakeholders in achieving efficient and resilient supply during crises.   Design/ Methodology/ Approach: Published reports and statistical records concerning the Russian-Ukrainian war and its impact on the supply chain disruption in Egypt are reviewed. Upon this, a focus group is conducted with the Egyptian stakeholders, including high-level participants from the government, and industrial representatives from the Egyptian Chamber of Commerce to investigate the current situation in Egypt. In addition, three semi-structured interviews with Egyptian market representatives, including representatives from the food sector, oil and gas sector, and the Egyptian tourism sector, help the Egyptian market stakeholders overcome those supply chain complexities.   Findings: They showed that the most affected markets are the food market, the tourism sector, and the oil and gas sector. Which, a SWOT analysis technique is used to show the major strengths, weaknesses, threats, and opportunities in the Egyptian market. In addition, a concluded road map is presented to producers and service managers to guide and upgrade their strategic plans to face any unexpected situations in the upcoming years and to show the gap to future researchers.   Research Implications/ Limitations: The Egyptian market stakeholders in food, oil, and gas, and tourism must implement new strategies for adapting to and dealing with crisis management, renovating production operations plans, and satisfying their market needs.   Originality: The paper is the first to provide a comprehensive analysis and evaluation of the impact of the crisis and the Russian-Ukrainian conflict on the Egyptian market, as well as new alternative and contingency plans to assist Egyptian stakeholders in mitigating its negative consequences.   Keywords: Russian-Ukrainian conflict, supply chain, Egyptian market.